The genus Cladophora Kutzing (Ulvophyceae) as a globally distributed ecological engineer - Zulkifly, Shahrizim; Graham, James M.; Young, Erica B.; Mayer, Robert J.; Piotrowski, Michael J.; Smith, Izak; Graham, Linda E. (Phycological Society of America, 2013)
The green algal genus Cladophora forms conspicuous nearshore populations in marine and freshwaters worldwide, commonly dominating peri-phyton communities. As the result of human activities, including the nutrient pollution of nearshore waters, Cladophora-dominated periphyton can form nuisance blooms. On the other hand, Cladophora has ecological functions that are beneficial, but less well appreciated. For example, Cladophora has previously been characterized as an ecological engineer because its complex structure fosters functional and taxonomic diversity of benthic microfauna. Here, we review classic and recent literature concerning taxonomy, cell biology, morphology, reproductive biology, and ecology of the genus Cladophora, to examine how this alga functions to modify habitats and influence littoral biogeochemistry. We review the evidence that Cladophora supports large, diverse populations of microalgal and bacterial epiphytes that influence the cycling of carbon and other key elements, and that the high production of cellulose and hydrocarbons by Cladophora-dominated periphyton has the potential for diverse technological applications, including wastewater remediation coupled to renewable biofuel production. We postulate that well-known aspects of Cladophora morphology, hydrodynamically stable and perennial holdfasts, distinctively branched architecture, unusually large cell and sporangial size and robust cell wall construction, are major factors contributing to the multiple roles of this organism as an ecological engineer.